Molecular detection of Hepatozoon spp. in Brazilian and exotic wild carnivores - Andre, M. R. [UNESP]; Adania, C. H.; Teixeira, R. H. F.; Vargas, G. H. [UNESP]; Falcade, M.; Sousa, L.; Salles, A. R.; Allegretti, S. M.; Felippe, P. A. N.; Machado, R. Z. (Elsevier B.V., 2010)
Hepatozoon spp. are apicomplexan parasites that infect a wide variety of animals. The infection occurs through the ingestion of a hematophagous arthropod definitive host. Herein, we assessed the presence of Hepatozoon spp. in 165 captive wild felids and 100 captive wild canids using molecular techniques. We found that 6 felids (4 little spotted cats, 1 jaguarondi, and 1 puma) and 5 canids (2 bush dogs, 1 fox, 1 crab-eating fox, and 1 maned wolf) were positive for Hepatozoon spp. Hepatozoon spp. may be a potential pathogen and an opportunistic parasite in immunocompromised animals or if occurring in concomitant infections. Because most Brazilian wild felids and canids are endangered, knowing whether Hepatozoon infection represents a threat for these animals is crucial. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Hepatozoon spp.; Wild canids; Wild felids; Brazil